Response of winter wheat to arbuscular mycorrhizal fungal inoculation under farm conditions - Bakonyi, István; Csitári, Gábor (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2018)
The effect of arbuscular mycorrhizal (AM) fungi inoculation was investigated on two winter wheat cultivars (Triticum aestivum var. Mv Nádor and var. Genius) grown under farm conditions in the neighbourhood of Nagyhörcsök in 2016. The soil was a chernozem with lime deposits (WBR classification: Calcic chernozem) with a mean humus content of 2.73%, AL-soluble P2O5 and K2O concentrations of 181 mg kg-1 and 149 mg kg-1 and a pH(KCl) value of 7.27. The AM inoculum contained reproductive units of Rhizophagus irregularis (previously Glomus intraradices) and Glomus mosseae (syn. Funneliformis mosseae). In addition to soil inoculation, some of the treatments were also given mineral fertiliser treatment (130 kg N ha-1, 78 kg P2O5 ha-1, 60 kg K2O ha-1).Both AM inoculation and mineral fertiliser treatment were found to have a significant effect on the yield (at the p
Keywords: AM fungi inoculation; Rhizophagus irregularis; Glomus mosseae; winter wheat; grain yield